Transparency and Accountability in Public Financial Reporting: Implementation and Challenges in the Digital Era: A Systematic Literature Review - Panggeso, Anastasia Gloria; Nirwana; Haliah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Government agencies are tasked with carrying out government operational activities. Transparency and public accountability are very important to prevent fraud that is detrimental to the country. For this reason, a system is needed that is able to increase optimal performance. Transparent and accountable financial management is the key to realizing good governance. Digital technology supports transparency in government reporting. Public sector accounting systems play an important role in providing relevant and reliable information, helping government institutions to be accountable for their performance to the public. The implementation of public sector accounting is expected to increase transparency, accountability and better decision making. This research highlights the importance of integrating public sector accounting to strengthen accountability and transparency in government organizations.